Comparison of methods for the detection of biofilm production in coagulase-negative staphylococci - Oliveira, Adilson [UNESP]; Cunha, Maria de Lourdes R. S. [UNESP] (Springer Nature, 2010)
Background: The ability of biofilm formation seems to play an essential role in the virulence of coagulase-negative staphylococci (CNS). The most clearly characterized component of staphylococcal biofilms is the polysaccharide intercellular adhesin (PIA) encoded by the icaADBC operon. Biofilm production was studied in 80 coagulase-negative staphylococci (CNS) strains isolated from clinical specimens of newborns with infection hospitalized at the Neonatal Unit of the University Hospital, Faculty of Medicine of Botucatu, and in 20 isolates obtained from the nares of healthy individuals without signs of infection. The objective was to compare three phenotypic methods with the detection of the icaA, icaD and icaC genes by PCR. Findings: Among the 100 CNS isolates studied, 82% tested positive by PCR, 82% by the tube test, 81% by the TCP assay, and 73% by the CRA method. Using PCR as a reference, the tube test showed the best correlation with detection of the ica genes, presenting high sensitivity and specificity. Conclusions: The tube adherence test can be indicated for the routine detection of biofilm production in CNS because of its easy application and low cost and because it guarantees reliable results with excellent sensitivity and specificity. © 2010 Cunha et al; licensee BioMed Central Ltd.